Respuesta :
(5.91×10^−3)⋅(8.7×10^10)
=(5.91 × 8.7)⋅(10^-3 × 10^10)
= 51.417 x 10^7
= 5.1417 x 10^8
hope it helps
=(5.91 × 8.7)⋅(10^-3 × 10^10)
= 51.417 x 10^7
= 5.1417 x 10^8
hope it helps
Answer:
Product [tex]5.1417 *10^{8})[/tex].
Step-by-step explanation:
Given : [tex](5.91* 10^{-3} )(8.7*10^{10})[/tex].
To find : What is the product written in scientific notation.
Solution : We have given
[tex](5.91* 10^{-3} )(8.7*10^{10})[/tex].
Combine like terms
[tex]5.91 * 8.7 * 10^{-3}*10^{10})[/tex].
[tex]51.417 * 10^{-3}*10^{10})[/tex].
[tex]51.417 *10^{7})[/tex].
In scientific notation
[tex]5.1417 *10^{8})[/tex].
Therefore, Product [tex]5.1417 *10^{8})[/tex].